Preliminary assessment of medical cannabis consumption by cancer survivors - Yuval Zolotov; Lia Eshet; Ofir Morag (Complementary Therapies in Medicine, 2021)
Objectives: To assess the motivation of cancer survivors to consume medical cannabis and to assess the patterns of use, perceived efficacy, as well as side and adverse effects. Methods: Cross-sectional survey among 190 Israeli cancer survivors who were licensed to use medical cannabis in a single institution. In addition to demographic information, the questionnaire examined patterns of use (including dosage, type of cannabis and way of administration), motivation for medical cannabis consumption, perceived efficacy, adverse and side effects, motivation for ceasing cannabis consumption, and tobacco smoking. Results: The mean monthly dosage of cannabis consumed was 42.4 grams; 95.8% of respondents reported not consuming cannabis regularly before being diagnosed with cancer; the most common way of administration was smoking, and most of the participants reported taking cannabis throughout the day. The most common symptoms for which participants took medical cannabis were pain (n = 169, 88.9%), sleeping disorder (n = 144, 75.8%) and anxiety (n = 79, 41.6%). Twenty patients (10.5%) reported on mild side (or adverse) effects. Conclusions: This study indicates that cancer survivors may indeed consume cannabis for symptom relief, and not merely for recreational purposes. Although our findings point to perceived safety and efficacy of medical cannabis for cancer survivors, more research is needed to study the adequate role that cannabis may have for treating symptoms associated with cancer survivorship.